Pemetaan Titik Penumpukan Sampah di Kota Lhokseumawe Menggunakan Metode Ant Colony Optimization - Suhaeymi, Rozzi Kesuma Dinata, Zara Yunizar (LPPM-UNIKI, 2023)
This research implements Ant Colony Optimization (ACO) to optimize waste collection routes in urban areas. The implementation utilizes the PHP, JS, and HTML programming languages, resulting in an interactive mapping application that facilitates community participation in identifying garbage accumulation locations. The research findings indicate that by employing ACO calculations with parameters α = 1.0 for pheromones and β = 2.0 for visibility, the best waste collection route was identified with a total distance of 9.565 km.The route begins at